Classroom Process and Practices in Public Pre-K Programs: Describing and Predicting Educational Opportunities in the Early Learning Sector. Issue 6 (18th August 2018) - Pianta, Robert C.; Whittaker, Jessica E.; Vitiello, Virginia; Ansari, Arya; Ruzek, Erik
ABSTRACT: Research Findings : The present study used data from 117 publicly funded preschool classrooms within a large, diverse, suburban county to describe teacher practices and child engagement along with classroom activity settings and children's exposure to instructional content. Practice or Policy : Results from this investigation revealed that children spent the largest share of the day in teacher-directed whole-group instruction and in free play and very little time was spent in individual and small-group settings. Although a 3rd of the school day was dedicated to academic activities, there were few opportunities for socioemotional learning, and children spent roughly a 3rd of the school day in routines/transitions and meals. Few differences emerged in the classroom observations across school- and community-based programs; however, more educated and experienced teachers spent more time teaching and in teacher-directed instruction.